Comprehensive analysis of equid herpesvirus recombination : an insight into the repeat regions - Tau, Rocio Lucia; Ferreccio, Carola Maria; Bachir, Natalia Veronica; Torales, Fatima Anabel; Romera, Sonia Alejandra; Maidana, Silvina Soledad (Elsevier, 2023)
High-throughput sequencing of genomes has expanded our knowledge of the Alphaherpesvirinae, a widely extended subfamily of DNA viruses that recombine to increase their genetic diversity. It has been acknowledged that Equid herpesvirus 1 (EHV-1) and equid herpesvirus 4 (EHV-4), two alphaherpesviruses with an economic impact on the horse industry, can recombine. This work aimed to analyze interspecific recombination between all equid alphaherpesvirus species, using genomes of EHV-1, EHV-3, EHV-4, EHV-6, EHV-8, and EHV-9 available in GenBank. 14 events of recombination by RDP4 and Simplot between EHV-1 x EHV-4, EHV-1 x EHV-9, EHV-8 x EHV-1, and EHV-8 x EHV-9 were identified. 10 out of 14 events involved ORF64, a double-copy gene located at the repeat regions that codifies for the infected cell protein 4 (ICP4). Among the ICP4, recombination can be found between EHV-1 X EHV-9, EHV-8 X EHV-9, and EHV-1 X EHV-4, the former affects zebra-borne genotypes, a type of EHV-1 that infect wild equids, and the latter match with previous breakpoints reported in fields isolates. Consequently, these findings strongly suggest that ICP4 is a hotspot for recombination. This work describes novel recombination events and is the first genome-wide recombination analysis using all available equid alphaherpesvirus species genomes.